2021
DOI: 10.1016/j.dcn.2020.100884
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in medial prefrontal and parietal cortex structure in children with disruptive behavior

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 110 publications
(128 reference statements)
0
11
0
Order By: Relevance
“…Supporting the notion that frontoparietal abnormalities are linked to aberrant functioning of the cognitive control network, structural MRI studies have shown reduced gray matter volumes in the ventral PFC ( Rogers and De Brito, 2016 ), as well as reduced cortical thickness and/or gray matter volume in the ventral PFC/orbitofrontal cortex and the supramarginal gyrus/inferior parietal cortex ( Smaragdi et al. , 2017 ; Ibrahim et al. , 2021 ), in children with disruptive behavior disorders relative to unaffected controls.…”
Section: Introductionmentioning
confidence: 93%
“…Supporting the notion that frontoparietal abnormalities are linked to aberrant functioning of the cognitive control network, structural MRI studies have shown reduced gray matter volumes in the ventral PFC ( Rogers and De Brito, 2016 ), as well as reduced cortical thickness and/or gray matter volume in the ventral PFC/orbitofrontal cortex and the supramarginal gyrus/inferior parietal cortex ( Smaragdi et al. , 2017 ; Ibrahim et al. , 2021 ), in children with disruptive behavior disorders relative to unaffected controls.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, although we included female and male participants in our study, the large majority of participants in both patient groups are males. While potentially reflecting the higher prevalence rate among males in both disorders (Loomes et al, 2017; Merikangas et al, 2010), sex differences have been described in both disorders (Fairchild et al, 2013; Ibrahim et al, 2021; Lai & Szatmari, 2020; Napolitano et al, 2022; Ypma et al, 2016). Our supplementary results are also indicative of a potential impact of sex on self‐reported AE, however, given the low numbers of females in the patient groups, results remain preliminary.…”
Section: Discussionmentioning
confidence: 99%
“…To form subgroups of youths with low and high CU traits, we used the clinical cutoff score of 30 as recommended by Docherty et al (2017) for the parent‐rated ICU. Therefore, the patient population was divided into a high ( N = 36 with CU traits ≥30) and a low ( N = 49 with CU traits <30) CU trait subgroup, while the TD group ( N = 45) remained the same (Ibrahim et al, 2021). The models were again separated for empathy scores obtained from either the self‐reported BES or the other‐reported GEM and contained CU subgroups as factor, AE and CE from either the BES or the GEM as regressor, as well as IQ, age, sex, data collection wave, and TIV as covariates.…”
mentioning
confidence: 99%
“…Parietal regions are implicated in memory and attention, and are recruited during cognitive control processes along with the ventral prefrontal cortex to modulate limbic reactivity 30,32,33 . Functional and structural MRI studies have shown that perturbations in parietal networks are associated with disruptive behavior in youths 2,3,34,35 , which includes regions of the supramarginal gyrus [34][35][36][37] . Because data-driven, connectomic approaches are advantageous for identifying highly predictive features, such as brain regions and networks, that were not hypothesized a priori, these approaches have potential to advance development of robust and generalizable biomarkers in childhood-onset psychiatric disorders 15,16 .…”
Section: Discussionmentioning
confidence: 99%